(untitled) (Research, Society and Development, 2022)
Resistance to antifungal agents is a problem in global health, and it is necessary to seek alternatives for control and treatment. There are scientific reports that show the potential for antifungal action of essential oils. The main objective of the research was to evaluate the sensitivity profile of C. albicans through the use of essential oils. It was an experimental study with a quantitative approach of the antifungal action of essential oils against the C. albicans ATCC strain, obtained commercially. The selection of essential oils was carried out through the recommendations of the Brazilian Pharmacopoeia. The strain was kept in successive repetitions in TSA culture medium, until use in the susceptibility tests. The antifungal activity of the essential oils was performed by the technique of diffusion in agar in wells. It was found that all essential oils were able to sensitize the C. albicans strain. With emphasis on C. cassia with formation of an inhibition halo of 40mm in diameter and lower potential for E. globulus with an inhibition halo of 12mm. The present study showed that the essential oils tested have antifungal properties on the C. albicans strain, however, with different susceptibility profiles. In addition, the data obtained allow expanding the knowledge about products of plant origin with antifungal potential. It is suggested that further research should be carried out in this line of investigation with the purpose of identifying other essential oils with this action and their phytoconstituents.